Penilaian Struktur Modal Dan Pengelolaan Modal Kerja - Ni Luh Eka Ayu Permoni; Ni Kadek Ayu Trisnadewi; Komang Somayasa (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2021)
The purpose of this study is to determine the assessment of capital structure and working capital management at the Mukti Singaraja Savings and Loan Cooperative. The data collection techniques used in this study used documentation techniques, namely financial statement data from 2014-2019. The data analysis technique used in this research is descriptive technique by calculating financial ratios first which is followed up with the analysis. The results of this study explain that the working capital turnover ratio has been very productive from year to year because the ratio is always above 100%. The cash turnover ratio is very efficient because the value of this ratio is above 100% even though the dominant cash turnover ratio value has decreased. The management of accounts receivable ratio which is assessed from the turnover of accounts receivable is very efficient because the value of accounts receivable turnover is always above the standard even though the dominant accounts receivable turnover ratio has decreased. The results of this study explain that the capital structure ratio based on assessment standards (Regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia No. 06 / Per / M.KUKM / V / 2006) is classified as bad. It can be seen that the DAR ratio value from year to year is always above the standard (> 80%), but it is always followed by an increase in the achievement of SHU. The assessment of the DER ratio is not good because the value of the DER ratio is always above the standard (> 200%) but this condition is always followed by an increase in the achievement of SHU